Retracing Hotbeds of the 1918–19 Influenza Pandemic. Spatial Differences in Seasonal Excess Mortality in the Netherlands - Rick J. Mourits; Ruben Schalk; Albert Meroño-Peñuela; Joe Raad; Auke Rijpma; Bram van den Hout; Richard L. Zijdeman (Historical Life Course Studies)
A century ago, the 1918–19 influenza pandemic swept across the globe, taking the lives of over 50 million people. We use data from the Dutch civil registry to show which regions in the Netherlands were most affected by the 1918–19 pandemic. We do so for the entire 1918 year as well as the first, second, and third wave that hit the Netherlands in summer 1918, autumn 1918, and winter 1919. Our analyses show that excess mortality was highest in Oost-Brabant, Zuid-Limburg, Noord-Holland, and Drenthe, Groningen, and Overijssel, whereas excess mortality was low in Zuid-Beveland, the Utrechtse Heuvelrug, and the Achterhoek. Furthermore, neighboring municipalities resembled one another in how severely they were affected, but only for the second wave that hit the Netherlands in autumn 1918. This non-random spatial distribution of excess mortality in autumn 1918 suggests that regional differences affected the spread of the disease.